Nucleotide probes for detection of candida species. - Chong, Pei Pei; Chieng, David Ching Soo; Seow, Heng Fong (2007)

(untitled)
The distinctive sequences of the Candida species internal transcribed spacer 2 regions are biotin-labeled and amplified for the subsequent species identification. Oligonucleotides which used as probes for identifying the Candida species are described. These oligonucleotides are useful in methods for the detection, identification, differentiation and diagnosis of Candida infection in a sample or subject.